HUBUNGAN PERAN PERAWAT SEBAGAI EDUKATOR DAN MOTIVATOR DENGAN KEPATUHAN MINUM OBAT PENDERITA TB DI POLIKLINIK MDR RUMAH SAKIT UMUM DAERAH DR. H. ABDUL MOELOEK - Muhammad Ricko Gunawan; Dayu Jaysendira (Universitas Malahayati Lampung, 2020)
ABSTRACT : RELATIONSHIP OF NURSE ROLE AS EDUCATOR AND MOTIVATOR WITH COMPLIANCE OF DRUG DRUG TB PATIENTS IN POLYCLINIC MDR HOUSE REGIONAL GENERAL ILLNESS Dr. H. ABDUL MOELOEK PROVINCE LAMPUNG Background : Lung Tuberculosis (Pulmonary TB) is one of the top 10 causes of death worldwide. Based on the results of the data it is known that in Lampung Province which has an MDR clinic only at the Regional General Hospital Dr. H. Abdul Moeloek, where the number of people suspected of drug resistant TB is 143 people. Waiting for 1 person to start treatment and 85 people for confirmation in treatment.Purpose : It is known the relationship of the role of nurses as educators and motivators with adherence to taking medication for TB patients at the MDR Polyclinic of the Regional General Hospital Dr. H. Abdul Moeloek Lampung Province in 2019.Methods : This research is a quantitative study, with a cross sectional type of research. Sampling by purposive sampling is based on the criteria desired by the researcher. Retrieving data using questionnaires distributed to respondents. The research was conducted in June - July 2019.Result : : It is known that some respondents were obedient in taking medication, as many as 42 (70.0%) respondents and most of them were not obedient in taking medicine, which was as many as 18 (30.0%) respondents. It is known that some respondents were obedient in taking medication, as many as 42 (70.0%) respondents and most of them were not obedient in taking medication, which was as many as 18 (30.0%) respondents. It was known by some respondents that the role of officers was a supportive motivator, as many as 36 (60.0%) respondents and most of the roles of officers were motivators who did not support, as many as 24 (40.0%) respondents. There is a relationship between the role of nurses as educators with adherence to taking medication for TB patients (p-value 0.011 OR 5.688). There is a relationship between the role of nurses as motivators with adherence to taking medication for TB patients (p-value 0.002 OR 7.327). Suggestions for providing education and counseling to the community regarding adherence to drinking oaru TB.Conclusion: there is a relationship between the role of nurses as educators and motivators of medication adherence in TB sufferers in Dr. H. Abdul Moeloek Lampung Province in 2019. Suggestions from researchers are expected to be more specific nurses in providing information about TB package drugs and nurses should also improve the quality of service to patients and provide motivation so that patients are motivated in their recovery. Keywords: the role of nurse, educators, motivators, obedience, tuberculosis INTISARI : HUBUNGAN PERAN PERAWAT SEBAGAI EDUKATOR DAN MOTIVATOR DENGAN KEPATUHAN MINUM OBAT PENDERITA TB DI POLIKLINIK MDR RUMAH SAKIT UMUM DAERAH DR. H. ABDUL MOELOEK PROVINSI LAMPUNG Pendahuluan: Penyakit Tuberkulosis Paru (TB Paru) merupakan salah satu dari 10 penyebab utama kematian di seluruh dunia. Berdasarkan hasil data diketahui bahwa di Provinsi Lampung yang memiliki klinik MDR hanya di Rumah Sakit Umum Daerah Dr H. Abdul Moeloek, dimana jumlah penderita terduga TB resisten obat sebesar 143 orang. Menunggu mulai pengobatan sebanyak 1 orang dan konfirmasi dalam pengobatan sebanyak 85 orang. Tujuan: Mengetahui hubungan peran perawat sebagai edukator dan motivator dengan kepatuhan minum obat penderita TB di Poliklinik MDR Rumah Sakit Umum Daerah Dr H. Abdul Moeloek Provinsi Lampung Tahun 2019.Metode: Penelitian ini merupakan penelitian kuantitatif, dengan jenis penelitian cros sectional. Pengambilan sampel secara purposive sampling yaitu berdasarkan kriteria yang diinginkan oleh peneliti. Pengambilan data menggunakan kuesioner yang dibagikan ke responden. Penelitian telah dilakukan bulan Juli 2019.Hasil: Diketahui sebagian responden patuh minum obat, yaitu sebanyak 42 (70,0%) responden dan sebagian besar tidak patuh minum obat, yaitu sebanyak 18 (30,0%) responden. Diketahui sebagian responden patuh minum obat, yaitu sebanyak 42 (70,0%) responden dan sebagian besar tidak patuh minum obat, yaitu sebanyak 18 (30,0%) responden. Diketahui sebagian responden peran petugas sebagai motivator yang mendukung, yaitu sebanyak 36 (60,0%) responden dan sebagian besar peran petugas sebagai motivator yang tidak mendukung, yaitu sebanyak 24 (40,0%) responden. Ada hubungan peran perawat sebagai edukator dengan kepatuhan minum obat penderita TB (p-value 0,011 OR 5,688). Ada hubungan peran perawat sebagai motivator dengan kepatuhan minum obat penderita TB (p-value 0,002 OR 7,327). Saran memberikan edukasi dan penyuluhan terhadap masyarakat mengenai kepatuhan minum oabat TB Paru.Kesimpulan: Ada hubungan antara peran perawat sebagai educator dan motivator terhadap kepatuhan minum obat pada penderita TB di RSUD Dr. H. Abdul Moeloek Provinsi Lampung tahun 2019. Saran dari peneliti diharapkan perawat lebih spesifik dalam memberikan informasi mengenai obat paket TB dan perawat juga harus meningkatkan mutu pelayanan kepada pasien dan memberikan motivasi agar pasien termotivasi dalam kesembuhannya. Kata kunci : peran perawat, edukator, motivator, kepatuhan, tuberkulosis